Pengembangan soal tes numerasi berbasis hierarchical content untuk fase A elemen bilangan dan aljabar - Hikmah Ramdhani Putri; Lalu Hamdian Affandi; Baiq Yuni Wahyuningsih; Iva Nurmawanti; Vivi Rachmatul Hidayati; Riska Wulandari (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Numeracy is an essential skill that students must master. The government administers the Minimum Competency Assessment (AKM) for Numeracy to map students’ numeracy abilities in Indonesia. However, in practice, the results of AKM have not fully guided teachers in determining appropriate instructional follow-up, as they only provide information on students’ proficiency levels without indicating which specific content has not yet been mastered. This study aims to develop a valid and reliable numeracy test instrument based on hierarchical content for primary school students. The development process followed several stages: defining the test, selecting a scaling method, constructing test items, conducting item trials, revising items, and preparing the final product. The instrument was tested on Grade 3 students at some Elementary School. Analysis of the learning outcomes produced five hierarchical content areas within the Numbers and Algebra element of Phase A, which were developed into ten test items. Rasch Model analysis indicated high reliability, and seven items were found to be valid (items 1, 3, 4, 7, 8, 9, and 10). This instrument is expected to help teachers identify not only students’ numeracy levels but also the prerequisite content that has not been mastered, thereby supporting more effective formative assessment.